Repurposing brucine as a chemopreventive agent in mammary gland carcinoma: Regulating lactate transport through MCT-4 - Asma Khatoon Zaidi; Anurag Kumar; Rohit Kumar; Jyoti Singh; Sneha Yadav; Archana Bharti Sonkar; Dharmendra Kumar; Neeraj Kumar Shrivastava; Mohd Nazam Ansari; Abdulaziz S. Saeedan; Gaurav Kaithwas (Toxicology Reports)
In the present study, we aim to identify a potential drug candidate that targets the Monocarboxylate Transporter-4 (MCT-4) protein. Syrosingopine (SRY) is a well-established inhibitor of lactate transport through MCT-4. We screened 2,11,192 potential leads through ZINC database, which were atleast 50 % structurally similar with SYR. After in-depth analysis, 900 molecules were shortlisted based on Lipinski's rule, optimal molecular weight, binding energy, hydrogen bonding, and ADMET (absorption, distribution, metabolism, excretion, and toxicity) properties that render them viable MCT-4 inhibitors. The outcome underscored Brucine (BRU) as the most promising lead molecule within a cohort of ten potential compounds. BRU is a monoterpenoid indole alkaloid and is used in the regulation of high blood pressure and other comparatively benign cardiac ailments. As such, no reports is available emphasizing the efficacy of BRU on lactate transport or mammary gland carcinoma. BRU demonstrated strong affinity for the MCT-4 transporter's catalytic domain, forming significant hydrophobic and polar interactions with essential amino acids at the binding site. BRU demonstrated significant cytotoxicity and increased the extracellular lactate levels in MCF-7 cells. The findings strongly encouraged BRU's effectiveness, offering promising paths for subsequent investigations.